A “willingness to be orchestrated”: Why are UK diplomats working with tobacco companies? - Alebshehy, Raouf; Silver, Karin; Chamberlain, Phil (Frontiers in Public Health, 2023)
Background The tobacco epidemic is global and addressing it requires global collaboration. International and national policies have been adopted to promote collaboration for tobacco control, including an obligation on diplomatic missions to protect public health from the vested interests of the tobacco industry. However, incidents of diplomats lobbying for the benefits of tobacco industry is still occurring despite these regulations. This paper presents a case study of a British ambassador engaging with the tobacco industry, and it points to some of the challenges researchers face in monitoring such incidents. Methods The incident studied in this paper was first identified through regular media monitoring conducted by the Tobacco Control Research Group at the University of Bath. The incident was further investigated by using the tools made available by the United Kingdom (UK) Freedom of Information Act, including submitting request, asking for internal review, and submitting a complaint to the Information Commissioner’s Office. Results We identified clear evidence of the UK ambassador to Yemen opening a cigarette factory, part owned by British American Tobacco (BAT), in Jordan. Our investigation revealed a lack of documentation of this and similar incidents of interaction between diplomats and the tobacco industry. We raise concerns about the actions of diplomats which contravene both national and international policies. Discussion Monitoring and reporting such activities produces several challenges. Diplomats’ interactions with the tobacco industry represent a major concern for public health as such interactions seem to be systematically repeated. This paper calls for action to better implement national and international policies to protect the public health including in low- and middle-income countries (LMICs).